COVID-19 vaccine acceptance and its association with knowledge and attitude among patients with chronic diseases in Ethiopia - Tilahun Degu Tsega; Abebaw Molla Kebede; Tadesse Miretie Dessie; Bezawit Adane; Melaku Yalew; Ahmed Fentaw Ahmed; Molla Getie Mehari; Gashaw Melkie Bayeh; Almaw Genet Yeshiwas; Mekuanent Asmare Yizengaw; Tamiru Alene; Zewdu Bishaw Aynalem (Taylor & Francis Group, 2024)
ABSTRACTCOVID-19 vaccine acceptance is crucial for patients with chronic diseases, but previous studies in Ethiopia have yielded inconsistent and inconclusive findings. To fill this gap, we conducted a systematic review and meta-analysis following established guidelines. Our search included relevant articles published between 2019 and 2023 from various sources. We assessed study heterogeneity and publication bias, and performed subgroup and sensitivity analyses. Our findings indicate that the COVID-19 vaccine acceptance rate among patients with chronic diseases in Ethiopia was 55.4%. We also found that good knowledge and a favorable attitude toward the vaccine were positively associated with the acceptance rate. Based on these results, we recommend that healthcare professionals, policymakers, and healthcare guide developers should work more to address the relatively low acceptance rate. Improving the knowledge and attitude further about the COVID-19 vaccines is crucial. Future research should include community-based and qualitative studies to enhance our understanding of vaccines acceptance.